Kebijakan Ekonomi pada Masa Dinasti Bani Umayyah - Patih, Husnama (Program Studi Ekonomi Syariah STAI Senori Tuban, 2023)
Since Rasulullah SAW died in 632 H, the Islamic government was made by Khulafaur Rasyidin, which was started by Abu Bakar and continued by Umar, Ustman to Ali bin Abi Talib. The appointment of the caliph over Khulafaur Rosyidin was a careless request based on deliberation to reach a consensus. Until finally after the death of Ali bin Abi Talib, the stick of the caliphate was taken over by Muawiyah bin Abu Sofyan from the Umayyads who became a turning point for the change in the government system from initial deliberation into an absolute monarchy. Muawiyah bin Abu Sofyan was a reliable politician, with his absolute monarchy system who was able to run the Umayyad government for 90 years from 41 H. / 661 AD to 132 H. / 750 AD. Because Muawiyah became caliph not from a deliberative system which was carried out during the Caliphate of Khulafaur Rosyidin period, this caused the division of the Muslims into several groups. However, we cannot deny all the progress that the Umayyad Caliphate made during its establishment in terms of politics, education, economy, and culture.